Effective executive's guide to PowerPoint 2000 : the seven steps for creating high-value, high-impact PowerPoint presentations - Nelson, Stephen L. (Redmond Technology P. RedmondUS, 2000)
Explains the workings and language of the PowerPoint programme. Shows how to outline content for presentation, and create, then add objects, for example, tables, charts, pictures to the outline. Provides helpful hints for starting and ending a presentation. Teaches how to use the built-in features such as design templates and colour schemes; and special effects, including sound and animation. Advises on aspects of preparation for delivering a presentation including: preparing handouts; creating speaker's notes etc. Looks at various presentation modes, for example, presenting in person; or via the web. Includes a glossary.